Lithoecotopes and vegetation of the Left-bank and the Right-bank dumps of the Southern Mining and Processing Plant - Voroshylova, Nataliia; Ворошилова, Наталія Володимирівна; Сhorna, Valentyna; Чорна, Валентина Іванівна; Dotsenko, Larisa; Доценко, Лариса Владленівна; Katsevych, Viktoria; Кацевич, Вікторія Валеріївна; Ananieva, Tamila; Ананьєва, Таміла Володимирівна; Harchenko, Kateryna; Харченко, Катерина (Дніпровський національний університет імені Олеся Гончара, 2023)
The article clarifies the peculiarities of the development of vegetation that is formed on the rock dumps of the Southern Mining and Processing Plant or their rock components (lithoecotopes), that is, only lithophilic vegetation. The problem of researching lithophilic plant communities from the point of view of forecasting their natural development and optimization is relevant not only for Kryvbas, but also for all industrial areas of open mining, in which significant masses of hard overburden rocks are brought to the surface of the earth. We have defined various lithoecotopes and described plant groups of varying complexity on plateau peaks, terraces and slopes depending on the specifics of their constituent rocks and typological features. Plant lithophilic groups of dumps of the Southern Mining and Processing Plant in accordance with the state of lithoecotopes, including all typological characteristics and geochemical nature of rocks, are marked by significant analytical (floristic and ecomorphic composition, occur- rence, stratification, physiognomy, abundance, coverage) and synthetic (similarity, constancy) differences signs A detailed study of thecondition of plants and their groups in lithoecotopes made it possible to make sure that their distribution and development have clearly defined substrate and relief-exposure dependencies, which can be used in phytotic and phytocenotic improvement of these man-made ecotopes. The natural overgrowth of all dumps has a mixed shrub-tree forest and grassy character in accordance with the typological characteristics and composition of the rocks. It was found that the change of plant communities on the lithoecotopes left without hu- man influence is endoexogenous in nature, because the ecesis external pressure is imposed on intracenotic processes. As a result of such integration, both fluctuations and successions naturally occur against the background of one or another substrate. The occurrence of species, the species and petrophytic capacity of plant communities, and their petrophytic indices in the lithoecotopes of the dumps have discrepancies depending on the specifics of the conditions. In general, the taxonomic composition of the plant communities of the dumps of the Pidennoy GZK of Kryvbas is determined by 218 species belonging to 54 families, 84 species of which are petrophytes. В статті з′ясовано особливості розвитку рослинності, яка формується на скельних відвалах Південного гірничозбагачувального комбінату або їх скельних складових (літоекотопах), тобто тільки літофільної рослинності. Проблема досліджень літофільних рослинних угруповань під кутом зору прогнозування їх природного розвитку та оптимізації є актуальною не тільки для Кривбасу, але й для всіх промислових районів відкритого видобутку корисних копалин, в яких на земну поверхню виносяться значні маси твердих розкривних гірських порід. Нами визначені різні літоекотопи та описані рослинні угруповання різної складності на платовидних вершинах, терасах і схилах в залежності від специфіки складаючих їх гірських порід та типологічних особливостей. Рослинні літофільні угруповання відвалів Південного гірночозбагачувального комбінату у відповідності до стану літоекотопів, включаючи всі типологічні характеристики та геохімічну природу гірських порід, відзначаються значними розбіжностями аналітичних (флористичний і екоморфічний склад, трапляння, ярусність, фізіономічність, ряснота, покриття) та синтетичних (схожість, константність) ознак. Деталізоване дослідження стану рослин і їх угруповань в літоекотопах дозволило переконатися, що їх поширення та розвиток мають чітко виражені субстратні та рельєфно-експозиційні залежності, що можливо використовувати в фітотичній і фітоценотичній меліорації цих техногенних екотопів. Природне заростання всіх відвалів має розріжено чагарниково-деревний лісний і травянистий характер відповідно до типологічних характеристик і складу порід. З′ясовано, що зміна рослинних угруповань на залишених без впливу людини літоекотопах носить ендоекзогенний характер, тому що ецезисний зовнішній натиск накладається на внутрішньоценотичні процеси. Внаслідок такої інтеграції на фоні того чи іншого субстрату закономірно реалізуються як флюктуації, так і сукцесії. Трапляння видів, видова та петрофітна ємкість рослинних угруповань, їх індекси петрофітності в літоекотопах відвалів мають розбіжності в залежності від специфіки умов. В цілому таксономічний склад рослинних угруповань відвалів Піденного ГЗК Кривбасу визначається 218 видами, які належать до 54 родин, з яких 84 види є петрофітами.
Літоекотопи та рослинність Лівобережних та Правобережних відвалів Південного гірничозбагачувального комбінату
Keywords: lithophilic groups; літофільні угруповання; taxonomic composition; таксономічний скла; phytorecultivation; фіторекультивація